2020
DOI: 10.1101/2020.07.27.223826
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

UNCG RNA tetraloop as a formidable force-field challenge for MD simulations

Abstract: Explicit solvent atomistic molecular dynamics (MD) simulations represent an established technique to study structural dynamics of RNA molecules and an important complement for diverse experimental methods. However, performance of molecular mechanical (MM) force fields (ffs) remains far from satisfactory even after decades of development, as apparent from a problematic structural description of some important RNA motifs. Actually, some of the smallest RNA molecules belong to the most challenging systems for MD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…In one of the two simulations we observe the transient formation of a U200–U205 base-pair capped by a canonical UUCG tetraloop fold . The low population of this state is not surprising, as the canonical UUCG tetraloop fold has been shown not to be stabilized to a sufficient degree within this force field . While the detailed architecture of the hexaloop has not yet been solved experimentally, , our computational prediction and available NMR data cannot be easily reconciled in this case.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…In one of the two simulations we observe the transient formation of a U200–U205 base-pair capped by a canonical UUCG tetraloop fold . The low population of this state is not surprising, as the canonical UUCG tetraloop fold has been shown not to be stabilized to a sufficient degree within this force field . While the detailed architecture of the hexaloop has not yet been solved experimentally, , our computational prediction and available NMR data cannot be easily reconciled in this case.…”
Section: Resultsmentioning
confidence: 74%
“…51 The low population of this state is not surprising, as the canonical UUCG tetraloop fold has been shown not to be stabilized to a sufficient degree within this force field. 52 While the detailed architecture of the hexaloop has not yet been solved experimentally, 11,32 our computational prediction and available NMR data cannot be easily reconciled in this case. We suggest that the simulations might be integrated with structural data collected in the future through a reweighting procedure.…”
Section: ■ Results and Discussionmentioning
confidence: 84%
“…In one of the two simulations we observe the transient formation of a U200-U205 base-pair capped by a canonical UUCG tetraloop fold [51]. The low population of this state is not surprising, as the canonical UUCG tetraloop fold has been shown not to be stabilised to a sufficient degree within this force-field [52].…”
Section: Stem Loop 5amentioning
confidence: 82%
“…In one of the two simulations we observe the transient formation of a U200-U205 base-pair capped by a canonical UUCG tetraloop fold ( Cheong et al, 1990 ), as also suggested by NMR measurements ( Wacker et al, 2020 ). The low population of this state is not surprising, as this fold has been shown not to be stabilised to a sufficient degree within this force-field ( Mráziková et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…32−34 It was suggested that these imbalances contribute to an improper dynamical description of r(UNCG) tetraloops and Z-DNA helices during MD simulations. 33,34 Standard van der Waals radii for nucleobase sp 2 carbons were also questioned, and a revision of Lennard-Jones (LJ) parameters of nucleobase atoms in the AFF was advocated. 35 Herein, we investigate the energetics of phosphate•••π contacts using quantum mechanics (QM) calculations with a dispersion-corrected double-hybrid density-functional approximation (DHDF-D3) and symmetry-adapted perturbation theory (SAPT) analysis and compare these results with those obtained by the classical AMBER force field (AFF).…”
Section: ■ Introductionmentioning
confidence: 99%